Determinants of Employee Performance at PT Iskandar Indah Printing Textile (Iskandartex), Indonesia - Retno Cahyani, Rusnandari; Kusumaningsih, Dyah Ayu; Kusumastuti, Anggit Dyah (Universitas Muhammadiyah Palembang, 2024)
This study aims to analyze the influence of compensation, work discipline, motivation, and work environment on employee performance at PT Iskandar Indah Printing Textile (Iskandartex). The research method used is descriptive quantitative with a survey approach. The population in this study comprises all weaving section employees at PT Iskandar Indah Printing Textile, with a sample of 100 respondents selected through a purposive sampling technique. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis was performed using multiple linear regression. The results indicate that compensation, work discipline, and motivation partially have a positive and significant effect on employee performance. However, the work environment does not have a significant effect on employee performance. Simultaneously, compensation, work discipline, motivation, and work environment have a significant effect on employee performance. The coefficient of determination (R2) of 0.341 indicates that 34.1% of the variation in employee performance can be explained by the four independent variables, while the remaining 65.9% is influenced by other factors not included in this study. This study suggests that companies should increase their focus on compensation, work discipline, and motivation to enhance employee performance. Additionally, even though the work environment does not show a significant effect, it is still important for companies to create a conducive work environment to support employee well-being and productivity.